Party Internal Conflict Management: A Study of The DPD Golkar Party and Gerindra Party DPD Bangka Belitung Island Province from 2010-2020 - Paizal Cholid Yahya; Ibrahim Ibrahim; Ranto Ranto (International Journal of Regional Innovation, 2022)
The study in this research discusses internal party conflict management in the case studies of the Golkar Party DPD and the Gerindra Party DPD of the Bangka Belitung Islands Province in the 2010-2020 period. There are at least three types of political conflicts that occur within the Gerindra and Golkar parties, especially in the Bangka Belitung Islands Province, as follows: Political conflicts due to fighting over political positions or power; Second, political conflicts due to political policies; Third, political conflicts arise because of different views on political institutions; The results of this study are that the conflict that occurred in the Golongan Karya Party internal DPD occurred in 2015 and the conflict that occurred in the Gerindra Party DPD occurred in 2018. The conflict in question is a conflict that occurred between social groups in the form of Marsidi H's dismissal Satar, Rina Fitriandari, Junaidi Thalib, and Hendra Apollo as well as the dismissal of Erzaldi Rosman Djohan as Chair of the DPD II Golongan Karya Party, Central Bangka Regency by Hidayat Arsani as Chair of the Golongan Karya Party DPD in the Golongan Karya Party DPD and conflicts that occur between social actors in the form of disputes between Deddy Yulianto as DPRD Bangka Belitung with Erzaldi Rosman Djohan regarding the change over time between party chairmen which was followed up to the realm of district court in Pangkalpinang City,Bangka Belitung Islands Province in the Gerindra Party DPD. Conflict management that occurred in the Golongan Karya Party DPD and the Gerindra Party DPD was carried out by referring to the statutes and bylaws. But on the other hand, conflict management that occurs is also carried out with reference to the policies of each party, where the Golongan Karya Party refers to the results of deliberations conducted by party cadres while the Gerindra Party refers to decisions from the central leadership council of each party which is also explained in the articles of the articles of association and bylaws.